2019
DOI: 10.1001/jamanetworkopen.2019.3755
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Thyroid Disorders and Colorectal Cancer Risk in Adult Patients in Taiwan

Abstract: Key Points Question Are thyroid disorders associated with colorectal cancer risk in an East Asian population? Findings In this case-control study that included 139 426 adults in Taiwan with or without a diagnosis of primary colorectal cancer, both hyperthyroidism and hypothyroidism appeared to be associated with a statistically significantly decreased risk of colorectal cancer diagnosis. Meaning Given these findings, it appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…The association between thyroid hormone and cancers has been investigated in many in vivo and in vitro studies, as early as 1896 when Beaston published on using thyroid extract to treat metastatic breast cancer in the Lancet (4,9,19,25,26). Specific alterations of thyroid hormone receptors (TRs) have been found in many different types of cancers, including breast cancer, and there are associations between TR expression and oncogene regulation (4,5,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The association between thyroid hormone and cancers has been investigated in many in vivo and in vitro studies, as early as 1896 when Beaston published on using thyroid extract to treat metastatic breast cancer in the Lancet (4,9,19,25,26). Specific alterations of thyroid hormone receptors (TRs) have been found in many different types of cancers, including breast cancer, and there are associations between TR expression and oncogene regulation (4,5,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6b illustrates the heatmap showing differences in expression levels of these biomarkers among the four CMS subtypes. As a result, we found that several statistically significant terms showed demonstrably closed relationships between COADREAD versus type I diabetes mellitus (hsa04940, adjusted P-value = 0.04, Supplementary Table S11) [24], versus autoimmune thyroid disease (hsa05320, adjusted P-value = 0.04, Supplementary Table S11) [25, 26], and versus Inflammatory bowel disease (hsa05321, adjusted P-value = 0.04, Supplementary Table S11) [27].…”
Section: Resultsmentioning
confidence: 99%
“…( 12) Interestingly, in a subgroup analysis for use of levothyroxine by patients with hypothyroidism, the association between hypothyroidism and a lower risk of CRC was no longer observed (adjusted OR 0.93 [0.66-1.30]). (12) In general, evidence linking CRC onset and levothyroxine intake remains controversial as distinct studies find varying results of the use of levothyroxine and the risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found evidence for a protective effect of levothyroxine, while others found no association. (10)(11)(12)(13) Furthermore, some of these 6 studies are limited by including a relatively small number of patients, relying on self-reported information, and lacking details on the dose and duration of levothyroxine use as well as tumour location and staging.…”
Section: Introductionmentioning
confidence: 99%